ANALISIS KUALITAS PELAYANAN, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PDAM KOTA KEDIRI - Dani , Frika Amalia Erika; Kurniawan, Rony (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of the study was to determine the impact of service quality, prices and products on customer satisfaction of PDAM Kediri City. Researchers use descriptive quantitative methods. There was a sample of 30 respondents of PDAM Kediri City service customers tested with multiple linear regression analysis. The researcher concluded that the quality of service, price, and product quality have a significant effect on consumer satisfaction. The novelty of this study is to add a variable previously studied by Joko Suwito entitled The Effect of Service Quality on Consumer Satisfaction at Cv.Global Ac Banjarbaru. While previous studies only had variables of service quality and customer satisfaction. Meanwhile, the novelty of the study is found in the variables of service quality, price, product quality, and consumer satisfaction.